A Streetcar Named "Derousal"? A Psychophysiological Examination of the Desire–Arousal Distinction in Sexually Functional and Dysfunctional Women. Issue 6 (23rd July 2016) - Sarin, Sabina; Amsel, Rhonda; Binik, Yitzchak M.
Abstract : Research indicates that desire and arousal problems are highly interrelated in women. Therefore, hypoactive sexual desire disorder (HSDD) and female sexual arousal disorder (FSAD) were removed from the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ( DSM -5), and a new diagnostic category, female sexual interest/arousal disorder (FSIAD), was created to include both arousal and desire difficulties. However, no research has tried to distinguish these problems based on psychosocial-physiological patterns to identify whether unique profiles exist. This study compared psychosocial-physiological patterns in a community sample of 84 women meeting DSM -IV (American Psychiatric Association, 2000 ) criteria for HSDD ( n  = 22), FSAD ( n  = 18), both disorders (FSAD/HSDD; n  = 25), and healthy controls ( n  = 19). Women completed self-report measures and watched neutral and erotic films while genital arousal (GA) and subjective arousal (SA) were measured. Results indicated that GA increased equally for all groups during the erotic condition, whereas women with HSDD and FSAD/HSDD reported less SA than controls or FSAD women. Women in the clinical groups also showed lower concordance and greater impairment on psychosocial variables as compared to controls, with women with FSAD/HSDD showing lowest functioning. Results have important implications for the classification and treatment of these difficulties.